Reverse logistics of waste electral and electronic equipment: proposal of a multilateral business platform (Research, Society and Development, 2020)
This paper aims to identify the necessary requirements for a multilateral platform that allows the indication and referral of WEEE, at the end of its useful life or unused, to places where it will be properly disposed of with a sustainable business model. This research has a technological nature, applied, aiming to produce the software platform design. The research took a qualitative approach as it sought to understand the needs of stakeholders in reverse WEEE logistics. The field study procedure was used to raise the necessary requirements for the platform and to understand how WEEE disposal works, in order to create a solution applicable to reality. The interviews were conducted in two cooperatives and one recycler, which serves several manufacturers, outsourcing reverse logistics to them. As for originality, no software platform with the proposed features and business model has been identified, either in the literature or in Internet research, although there are applications for this follow-up. Based on the requirements raised in the field study, a minimum viable product (MVP) of the multilateral platform called REEEcicla was developed, together with a business model. MVP has been tested with two cooperatives and one OSCIP. There was no opportunity for consumer testing. In terms of theoretical / methodological contributions, the article uses an interdisciplinary approach and proposes a practical and innovative application of the use of a technological platform and a business model to improve the treatment of WEEE.